ANALISIS PENGARUH ALOKASI JUMLAH KREDIT TERHADAP LIKUIDITAS PADA PT BANK NIAGA Tbk - Ende, Ende (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2021)
This research was conducted to determine the effect of credit allocation on the liquidity (cash ratio) of PT. Bank Niaga is open. The data used are annual financial reports (2015 to 2019) obtained from the Jakarta Stock Exchange Capital Market Reference Center. In addition, studies or reviews from various sources of literature related to these problems are also carried out. The composition of credit and cash ratio owned is Rp. 7.94 trillion with 6.46% in 2015, Rp. 11.76 trillion with 6.51% in 2016, Rp. 14.41 trillion with 6.42% in 2017, Rp. 21.09 trillion with 7.75% in 2018 and Rp. 29.31 trillion with 8.60% in 2019. Bank Niaga’s open credit allocation policy is considered to be very optimal and its liquidity has met the minimum cash ratio of 2%, so it is classified as a bank with good liquidity